Expression of Yap Signaling Hippo Pathway in Cervical Pre-cancerous Lesions and Cervical Cancer - Rizal, M Masrur; Arifa Mustika; Wita Saraswati (Indonesian Journal of Obstetrics and Gynecology, 2024)
Abstract Objective: To determine the expression of YAP in cervical pre-cancerous and cervical cancer lesions.Methods: Researchers systematically searched five databases using the checklist for Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) guideline and Newcastle-Ottawa Scale (NOS).. Inclusion criteria were the original study of YAP expression in cervical pre-cancerous lesions and cervical cancer, observational and experimental study, and using immunohistochemical techniques. The study protocol was registered in the PROSPERO database of systematic review (IDCRD42023407469). Results: The data search in this study followed the PRISMA Guideline, which includes phases of identification, screening, and inclusion of studies. Initially, 245 articles were identified across five databases: Pubmed (105), ScienceDirect (8), Scopus (29), Web of Science (26), and ProQuest (77). After removing duplicates, 157 studies remained. During the initial screening, 142 studies were excluded, leaving 15 studies for further evaluation. These were assessed based on the use of immunohistochemistry staining for YAP expression and staining result. Subsequently, ten studies were excluded for either not using immunohistochsmistry or lacking staining result, resulting in five studdies selected for qualitative analysis. These five studies were evaluated using the New Ottawa Scale, as detailed in Table 1, and their YAP Expression characteristics are summarized in Table 2. Conclusion: This systematic review showed that YAP expression at all levels ranging from normal tissue, cervical intraepithelial neoplasia, squamous cell carcinoma, and adenocarcinoma had increased expression in the cytoplasm or cell nucleus following the development of cervical cancer and tumorigenesis influenced by intra-tumor heterogeneity for YAP expression. YAP is expressed in the cytoplasm and nucleus, with different functions. YAP expression in these two sites Excessive YAP expression will trigger epithelial changes into mesenchyme which also plays a role in cancer development. This YAP expression also correlates with HPV, in which YAP levels will be maintained and increased.Keywords: cervical cancer, cervical pre-cancerous lesions, YAP expression.